Analisis dan simulasi debit banjir dengan variasi koefisien limpasan menggunakan HEC-RAS - Ade Tricia Miranda (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2025)
Floods have a damaging impact on at-risk areas such as areas with relatively high land cover, especially after heavy rains. Land cover is the influence of land use. In land use, the runoff coefficient (C) is a factor that greatly affects the amount of water runoff that occurs during and after rain. The runoff coefficient (C) describes how large the proportion of rainwater that will flow as surface runoff compared to the water that seeps into the soil, so, the closer the coefficient value is closer to the value of 1, the more an area is unable to absorb water, as well as if the runoff coefficient (C) is closer to 0, the more an area can absorb water well. The runoff coefficient (C) has a high correlation with land use. In this study, the variation of runoff coefficient (C) will be simulated on rainfall and area using rational equations and then the results are simulated using HEC-RAS. The variation in runoff coefficient (C) was simulated with the criteria conditions of cultivated land, clay & silt loam soils (C= 0.4) and regional conditions when only able to overflow water or unable to absorb (C= 1). The results were found that the runoff coefficient (C) affects the area and depth of flooding in the study area. At C = 0.4 the maximum flood depth is 2.99 meters in the upstream part of the river and 1.65 meters downstream, while when C = 1, the maximum flood depth is 2.03 meters in the upstream part and 1.1 meters in the downstream part. In this case, it is important to prepare rainwater reservoirs in areas with relatively high land cover or runoff coefficient (C).